Pemanfaatan Vermikompos Yang Berbeda Terhadap Perubahan Parameter Kimia Pada Media Tanah Gambut - Purba, Constantine; Hasibuan, Saberina; ', Syafriadiman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted from January to March 2017 located atPeat Moss Village of Kualu Nenas, District of Tambang, Kampar, Riau. The aimof this study was to know the best type of vermicompost to change the chemicalparameters of peat soil as pond bottom soil such as pH, soil organic matter content(KBOT), total N, total P, total K, C/N ratio and water chemical parameters such aspH, Dissolved oxygen (DO), Free carbon dioxide (CO2), Nitrate, Orthophosphateand Ammonia. The method used in this study was an experimental method byusing Completely Randomized Design (RAL) of one factor with four treatmentsand three replications. The treatments in this study were without vermicompost(P0), human vermicompost (P1), cow vermicompost (P2), chicken vermicompost(P3).The results showed that best treatment during the study was P1 (humanvermicompost) with pH 6.47, KBOT 59.69%, total N 2.79%, total P 2.33%, totalK 1.53% and C/N ratio 16.59. Furthermore, for the range of water chemistryparameters during the study was still good with pH ranges from 5.6 to 6.8, DOranged from 2.3 to 3.3 mg/L, CO2 ranged from 9.96-18.99 mg/L, nitrate 10,43mg/L, orthophosphate 6,76 mg/L, ammonia 0.08 mg/L.Keyword: Vermicompost, chemical parameters, peat soil